1996
DOI: 10.1136/gut.39.2.199
|View full text |Cite
|
Sign up to set email alerts
|

Small intestinal permeability to mannitol and lactulose in the three ethnic groups resident in west Birmingham.

Abstract: Background/Aims-Asymptomatic resi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
1
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 20 publications
0
16
1
1
Order By: Relevance
“…In Sudan, increased intestinal lactulose/mannitol permeation was found in 10 apparently healthy residents compared with 33 normal subjects from the UK26; in Israel,28 a wide range of 51 Cr-EDTA permeation was found in control subjects which may reflect the presence of tropical enteropathy in the Middle East. Asymptomatic subjects from India and the Carribean resident in Birmingham, UK, showed a higher lactulose/mannitol excretion than resident white subjects,23 which accorded with intestinal morphology 22. As the ethnic groups mentioned were not studied while resident in both temperate and tropical countries, comparisons required to establish the aetiological importance of ethnic versus geographical factors were not possible.…”
Section: Discussionmentioning
confidence: 99%
“…In Sudan, increased intestinal lactulose/mannitol permeation was found in 10 apparently healthy residents compared with 33 normal subjects from the UK26; in Israel,28 a wide range of 51 Cr-EDTA permeation was found in control subjects which may reflect the presence of tropical enteropathy in the Middle East. Asymptomatic subjects from India and the Carribean resident in Birmingham, UK, showed a higher lactulose/mannitol excretion than resident white subjects,23 which accorded with intestinal morphology 22. As the ethnic groups mentioned were not studied while resident in both temperate and tropical countries, comparisons required to establish the aetiological importance of ethnic versus geographical factors were not possible.…”
Section: Discussionmentioning
confidence: 99%
“…publications on increased intestinal permeability in cases with Crohn's disease is contradicted by others [5].…”
mentioning
confidence: 96%
“…In 1996, Iqbal et al [5] reported that the lactulose/mannitol excretion ratio (LMER) in white healthy subjects was 0.022 (median). This was similar in comparable dyspeptic white patients but it was different in Indian (0.031) and Afro-Caribbean (0.033) patients with dyspepsia.…”
mentioning
confidence: 99%
“…Normally, an intact intestinal epithelial barrier will not allow molecules as large as albumin to pass, and the endothelial barrier would also partly restrict this. However, in conditions where the intestinal barrier integrity may be injured, endothelial and epithelial permeability could be increased, whereby studies on intestinal barrier function are needed [140]. …”
Section: Marker Difference and Significancementioning
confidence: 99%
“…From the 1980s, the separate role of endothelial and epithelial barriers in intestinal permeability has been investigated. Macromolecular- and micromolecular-sized markers were used to separately assess intestinal endothelial and epithelial barrier permeability, but the optimal method to be used in the clinical situation has yet not been found [140]. …”
Section: Recognition Of Permeabilitymentioning
confidence: 99%